Expanding Marketing Empirical Generalisations to Health Behaviours: Physical Activity is Not so Different from Buying Behaviour, after-All. Issue 4 (November 2017) - Wilson, Amy L.; Sharp, Byron; Nguyen, Cathy; Bogomolova, Svetlana
The Negative Binomial Distribution (NBD) is a model that describes consumer purchase frequency over time. This paper tests the applicability of this model to a novel context: physical activity behaviours (using data obtained from Australia, the United States, and Singapore). The fit of the NBD to the data demonstrates that physical activity behaviour is consistent with other consumer behaviour patterns. Within a one-week period, the majority of people are either non- or light-engagers of the different intensities of leisure-time physical activity. Yet, people are not 'active' or 'inactive', rather, degree of engagement varies. Infrequency of reported levels and variety of physical activities might be due to health promotion having a strong focus on rational persuasion and less focus on mass communication that builds mental availability. Our contribution broadens the applicability of the NBD showing it can be helpful for those seeking to promote health behaviours, not just purchases.